The influence of remuneration, work environment, and career development on Generation Z's job application intention mediated by company reputation - Lesmono, Putra; Widhianto, Chandra Wibowo (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to analyze the influence of remuneration, work environment, and career development on Generation Z's intention to apply for jobs, mediated by company reputation in the Jakarta region. The research design is quantitative. The data collection will be conducted through a survey method using a questionnaire as the primary data collection tool from a population sample, and the research design will be quantitative. Based on the test results, it can be concluded that the research model meets the composite reliability and Cronbach's alpha criteria and is considered reliable. The results of this study show that company reputation mediates the influence on Job Application Interest among Generation Z, with company reputation being the mediating factor.